An alumni study of a Master's in international health. (April 2020) - Kismul, H.; Hasha, W.; Hinderaker, S.G.; Moen, B.E.
Abstract: Objectives: The objective of the study was to clarify the reasons why students who graduated from a Master's programme in international health were joining the programme. Another objective was to document how the Master's degree had influenced the careers of the graduates. Study design: An online survey of students who graduated from a Master's programme in international health, including oral science, between 2010 and 2015. Method: The study used an anonymous questionnaire that contained 28 items. Topics included information such as demographics, questions about the reasons for joining the Master's programme and the benefits and influence of the programme on the career of the students. Results: Of the 102 alumni who were invited to participate, 70 responded. The response rate was 69%, and we have no information about the non-responders. The results showed that the main reasons for students enrolling in the programme were to improve their competence and develop their career. Around 63% of the respondents reported that the programme had increased their competencies in the jobs they had, whereas 24% answered that their increased qualifications had enabled them to acquire new positions. Thus successfully completing the programme had a positive influence on the graduates' careers in international health. Most of the graduates, who were working, were typically employed at hospitals and universities. Several graduates had proceeded to gain further qualifications by now being enrolled in a PhD programme. Conclusions: Among the 70% of responders in this survey, the master's programme had benefitted the alumni and the programme had fulfilled their expectations. The programme had a positive influence on the alumni in areas such as increased competency, development of their careers, new positions and better salaries. Highlights: Alumni reported that the master's programme had increased their competencies in the jobs they had. Alumni had increased qualification, and this had enabled them to acquire new positions. The master's programme had positive impacts on graduates' careers in both international health and oral sciences. The graduates who were working were typically employed at hospitals and universities. Several graduates went on to take further qualification by enrolling to take a PhD.